YOUTH RESILIENCE IN CLIMATE-RELATED DISASTERS: A BIBLIOMETRIC AND MAPPING APPROACH - Zahri, Rafizah; Ali, Abd Halim Md; Ahmad, Yarina (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The growing number and severity of climate-related disasters highlight the pressing need to understand how young populations develop resilience in the face of environmental crises. Despite the growing recognition of youth as both vulnerable and resourceful actors in disaster risk reduction, systematic evidence mapping of this domain remains limited. This research discusses the gap by conducting a bibliometric analysis on the theme of Youth Resilience in Climate-Related Disasters using data sourced from the Scopus database. This research aims to resolve the fragmented knowledge and lack of consolidated insights into global research trends, collaborations, and thematic structures in this emerging field. The methodology involved four key steps: first, data collection through Scopus advanced searching using the keywords “youth,” “resilience,” and “disaster,” yielding a final dataset of 665 documents (2005–2025); second, data analysis using Scopus Analyzer to generate statistical trends and graphical outputs; third, data cleaning and harmonisation using OpenRefine to ensure accuracy and consistency; and fourth, visualisation of co-authorship, keyword co-occurrence, and country collaboration networks through VOSviewer. The numerical results revealed a steady growth in publication trends, peaking in 2025, with the United States, United Kingdom, as well as Australia emerging as the leading contributors. Meanwhile, developing countries such as Indonesia, Bangladesh, and Malaysia demonstrated increasing yet comparatively limited contributions. Co-occurrence keyword mapping generated six distinct clusters, highlighting the dominance of themes such as mental health, community resilience, disaster preparedness, and coping strategies among youth. Furthermore, co-authorship analysis indicated strong international collaboration, with developed countries serving as central hubs of knowledge exchange. To conclude, this bibliometric research contributes to the body of knowledge by consolidating fragmented research, identifying influential works, visualising global collaboration networks, and highlighting future directions. The findings reinforce the importance of youth-centred resilience strategies in climate-related disaster contexts and provide a comprehensive reference point for researchers, policymakers, and practitioners seeking to strengthen disaster preparedness and adaptation frameworks.